2019
DOI: 10.1002/1873-3468.13463
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive TORC1 sensitizes yeast cells to endoplasmic reticulum stress by compromising cell wall integrity

Abstract: Edited by Michael IbbaAccumulation of misfolded proteins in the endoplasmic reticulum (ER) activates the unfolded protein response (UPR). Here, we investigated how the target of rapamycin complex 1 (TORC1) signaling cascade acts in parallel with the UPR to regulate ER stress sensitivity. Using Saccharomyces cerevisiae, we found that TORC1 signaling is attenuated during ER stress and constitutive activation of TORC1 increases sensitivity to ER stressors independently of the UPR. Transcriptome analysis revealed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 110 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Opi1 has been shown to be a substrate for PKA phosphorylation, which enhances its activity as a repressor of INO1 [73]. Moreover, it was previously demonstrated that a hyperactive variant of the TORC1 kinase complex (TOR1 L2134M allele) reduced the expression of INO1 [74]. Based on the results reported in this manuscript, we posit that weakened electrostatic interaction of Opi1 with PA promoted by decreased cytosolic pH is sufficient to favor Opi1 repressor activity and reduce INO1 transcription (Figure 6A), and confer an inositol auxotrophy phenotype (Figure 5E), thus leading to LD dyshomeostasis (Figure 6B).…”
Section: Uncoupling Opi1 Activity From Pa Binding Is Sufficient To Induce Inositol-dependent Phenotypes and Ld Generationmentioning
confidence: 99%
“…Opi1 has been shown to be a substrate for PKA phosphorylation, which enhances its activity as a repressor of INO1 [73]. Moreover, it was previously demonstrated that a hyperactive variant of the TORC1 kinase complex (TOR1 L2134M allele) reduced the expression of INO1 [74]. Based on the results reported in this manuscript, we posit that weakened electrostatic interaction of Opi1 with PA promoted by decreased cytosolic pH is sufficient to favor Opi1 repressor activity and reduce INO1 transcription (Figure 6A), and confer an inositol auxotrophy phenotype (Figure 5E), thus leading to LD dyshomeostasis (Figure 6B).…”
Section: Uncoupling Opi1 Activity From Pa Binding Is Sufficient To Induce Inositol-dependent Phenotypes and Ld Generationmentioning
confidence: 99%
“…Moreover, the relationship among ER stress, cell wall integrity and various signaling cascades has been reported in different fungi. These signaling cascades are exemplified by the target of rapamycin (TOR) and calcium/calcineurin pathways [74][75][76]. In this study, we indicated that the Mkc1 MAPK pathway is involved in the Sfp1-regulated cell response to LL-37 (Figure 2C).…”
Section: Discussionmentioning
confidence: 60%
“…In F. oxysporum , the cell wall is mainly composed of glucans, chitin, and glycoproteins (Schoffelmeer et al, 1999) and its integrity is essential for development and virulence (Fernandes et al, 2021; Martin‐Udiroz et al, 2004; Nunez‐Rodriguez et al, 2020). Interestingly, S. cerevisiae cells expressing a hyperactive TOR1 allele were impaired in ÎČ‐1‐3‐glucan synthesis and exhibited increased sensitivity to cell wall‐perturbing compounds (Ahmed et al, 2019). Furthermore, in F. graminearum loss of Sit4, a phosphatase that is inactivated by TORC1, caused increased sensitivity to cell wall‐damaging agents and to high temperature stress (Yu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%